2001
DOI: 10.1136/pmj.77.912.650
|View full text |Cite
|
Sign up to set email alerts
|

Formal education programmes for senior house officers: comparison of experience in three hospital specialties

Abstract: This study was designed to compare the attendance rate of senior house oYcers (SHOs) in three specialties at formal educational events, examine experiences of protected time, use of educational objectives, and perceived barriers to attendance and evaluate diVerences found in the context of variations in training practice within each specialty. A quantitative questionnaire survey was completed by Trent region SHOs in obstetrics and gynaecology, general medicine, and accident and emergency posts. An independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The second most common reason SpRs gave for not attending teaching was clinical duties on the ward, in A&E or in outpatient clinics, implying that scheduled teaching was not truly protected and ‘bleep‐free’. This has previously been noted to affect junior doctors in general medicine, and obstetrics and gynaecology, but not those in A&E, where formal educational activities had been integrated successfully into a shift pattern of working 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second most common reason SpRs gave for not attending teaching was clinical duties on the ward, in A&E or in outpatient clinics, implying that scheduled teaching was not truly protected and ‘bleep‐free’. This has previously been noted to affect junior doctors in general medicine, and obstetrics and gynaecology, but not those in A&E, where formal educational activities had been integrated successfully into a shift pattern of working 7 …”
Section: Discussionmentioning
confidence: 99%
“…This has previously been noted to affect junior doctors in general medicine, and obstetrics and gynaecology, but not those in A&E, where formal educational activities had been integrated successfully into a shift pattern of working. 7 Comments from SpRs suggest that there is discordance between what consultants and SpRs consider to be teaching or learning. Formal structured teaching activities such as grand rounds (formal presentation of selected cases, including discussion points and literature search), departmental meetings and case presentations may be timetabled as teaching but are not considered as such by SpRs if these events are not focused on SpR learning objectives, or are not bleep-free.…”
Section: Self-directed Learningmentioning
confidence: 99%
“…Previous studies looking at junior doctors' working patterns have used similar numbers of house officers, 2,3 but no study has carried out a direct comparison between two time periods as far apart as 4 years. Studies have suggested that it is possible to implement the shift system successfully with improved quality of life for doctors, 4 better education, 5 and more opportunities for flexible training. The detrimental effect on training is, however, well documented [6][7][8] with some of the studies reporting increased job dissatisfaction 8 and a reduction in quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…15 Similarly, Flett et al reported that in general medicine service commitments were a major obstacle to attendance at formal educational sessions in the Trent region. 16 Hopefully, some of these issues will be addressed by initiatives such as the ''Changing Workforce'' programme, 17 which is currently reviewing the roles of staff groups within the NHS.…”
Section: Nhs Service Commitmentsmentioning
confidence: 99%
“…21 22 To improve access to the linear curriculum a model of integrating formal educational programmes within the shift pattern has been shown to be workable 16 in an accident and emergency setting. A different model may be to structure a programme of educational modules repeated on several occasions to accommodate individual shift patterns.…”
Section: Linear Curriculummentioning
confidence: 99%